0275 An Ergonomic Assessment: Occupational Health and Safety Risk Factors of Commercial Cafeteria Workers. (23rd June 2014) - Bhatt, Hema; Sharma, Promila
Abstract : Objectives: Kitchen work is demanding, both physically and mentally. The employees work under pressure of time and perform various parallel tasks, many of which include exposure to a combination of risk factors of MSDs. This study was conducted for ergonomic assessment of commercial kitchen workers working in university hostel cafeteria Method: A survey of 40 workers employed at university hostel cafeteria at G. B Pant University of Agriculture and Technology at Uttarakhand state in India was carried out. Self administered questionnaire, interviews and observations were used as research instruments to collect data. Results: It was found that there exists some major risk factors including repetition, awkward postures, force exertion, static posture, mechanical contact stress, temperature and vibration at these commercial kitchen workstation. 77.5 percent respondents were found to be involved in 5–8 h, 15 per cent of respondent were found to be involved for 9–12 h and 7.5 percent of the respondents were found working for 13–16 h. Nearly all the workers felt pain in neck, shoulders, wrist, elbow, knee, and ankle, upper and in lower back. Conclusions: An ergonomically designed workstation reduces the human efforts, enhances the work efficiency and at the same time provides the safety to the worker. Kitchen workers should be given awareness about the advantages and disadvantages of the good ergonomic practices so as to reduce the occupational health hazards and increase productivity.